Mekanisme Pembiayaan Mudharabah pada Usaha Mikro Kecil Menengah (UMKM) di BMT NU Cabang Senori - Ilmiyah, Izzatul (Journal of Islamic Finance and Syariah Banking, 2023)
This research discusses "Financing Mechanisms Mudharabah in Micro, Small and Medium Enterprises (MSMEs) at BMT NU Senori Branch". The aim of this research is to determine the financing mechanism mudharabah on Micro, Small, and Medium Enterprises (MSMEs) at BMT NU Senori Branch and Financing Analysis mudharabah in Micro, Small, and Medium Enterprises (MSMEs) at BMT NU Senori Branch based on DSN-MUI fatwa No.07/DSN-MUI/VI/2000. In this research, researchers used qualitative research. The research results show that the financing mechanism mudharabah At the BMT NU Senori branch is carried out in various stages, starting from the application for financing by the customer to the final stage, namely the disbursement of the funds that will be brought by the customer. And financing analysis mudharabah in Micro, Small, and Medium Enterprises (MSMEs) at BMT NU Senori Branch based on the DSN-MUI fatwa No.07/DSN-MUI/VI/2000 shows that the financing applied at BMT NU is in accordance with what has been stipulated in the DSN-MUI fatwa. It's just that there is a slight difference, namely that the DSN-MUI fatwa stipulates "the length of time the business will be carried out, the procedures for withdrawing funds, and the percentage for sharing profits agreed upon by both parties (BMT and the business manager)" whereas in reality at the BMT NU Senori branch, financing mudharabah provided by BMT NU to its customers or members, in this case including business actors, regarding the procedures for withdrawing funds determined by BMT in accordance with the ceiling size and characteristics of the financing proposed by prospective customers.